Seanmhair. - John, Hywel (Oberon modern plays., 2017)
A chance meeting between two children on the streets of Edinburgh leads to a terrible reckoning, leaving Jenny and Tommy forever bound together by blood and fate. Brutal and beautiful, Hywel John's remarkable new play glimmers and cuts like a jewel, fusing raw epic romance with guttural urban poetry to tell the story of a secret generational legacy of love, violence and fury.